2020
DOI: 10.1088/1674-4926/41/6/062701
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of mono-crystalline silicon solar cells with passivated emitter and rear contact configuration for the efficiency beyond 24% based on mass production technology

Abstract: Mono-crystalline silicon solar cells with a passivated emitter rear contact (PERC) configuration have attracted extensive attention from both industry and scientific communities. A record efficiency of 24.06% on p-type silicon wafer and mass production efficiency around 22% have been demonstrated, mainly due to its superior rear side passivation. In this work, the PERC solar cells with a p-type silicon wafer were numerically studied in terms of the surface passivation, quality of silicon wafer and metal electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The proficient charge extraction usually suppresses bimolecular recombination and contributes to the improvement of photovoltaic performance. [ 53–55 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proficient charge extraction usually suppresses bimolecular recombination and contributes to the improvement of photovoltaic performance. [ 53–55 ]…”
Section: Resultsmentioning
confidence: 99%
“…The proficient charge extraction usually suppresses bimolecular recombination and contributes to the improvement of photovoltaic performance. [53][54][55] To evaluate the charge recombination aforementioned, transient photovoltage (TPV) spectra were implemented. As depicted in Figure 5d, PF2:m-ITIC devices present a prolonged lifetime of ≈1.77 μs compared to PT-E:m-ITIC devices (0.84 μs) and PF1:m-ITIC devices (1.12 μs), implying the charge recombination rate is significantly reduced in the former sample.…”
Section: Charge Dynamicsmentioning
confidence: 99%
“…This is the passivating emitter and rear cell (PERC) solar cell architecture, which has become the mainstream technology in photovoltaic manufacturing in recent years. The performance of PERC cells has grown rapidly with record efficiencies in excess of 24% reported in research and development, [ 2 ] while values in the range of 22–23% have been demonstrated in mass production. [ 3 ] Recent research showed that the highest energy conversion efficiency ( η ) potential of PERC (≈24.5%) is limited by recombination in the p‐type c‐Si base and the phosphorus‐doped front emitter.…”
Section: Introductionmentioning
confidence: 99%
“…Organic–inorganic halide perovskite photovoltaic technologies have demonstrated an unprecedented progress in less than a decade with power conversion efficiency (PCE) of 25.5%, approaching the record of monocrystalline silicon devices . Interests have arisen in the commercialization as well as the extension of the perovskite photovoltaic technologies for a new scope of green energy utilization and storage .…”
mentioning
confidence: 99%
“…O rganic−inorganic halide perovskite photovoltaic technologies have demonstrated an unprecedented progress in less than a decade 1 with power conversion efficiency (PCE) of 25.5%, approaching the record of monocrystalline silicon devices. 2 Interests have arisen in the commercialization as well as the extension of the perovskite photovoltaic technologies for a new scope of green energy utilization and storage. 3 For example, the proposed concept of using perovskite solar cells (PSCs) to drive water splitting reactions for oxygen or hydrogen generation has opened up a new route toward efficient solar energy conversion into fuels that are easier for storage.…”
mentioning
confidence: 99%